Antibiotics as Anti-Inflammatory and Immunomodulatory Agents - Rubin, Bruce K.; Tamaoki, Jun (Progress in Inflammation Research, 2005)
Although the potential for immunomodulation has been recognized for many years there has been an explosion of data in this field with relevance especially to the treatment of chronic airway diseases. Most of the work in this field has been conducted by Japanese investigators but in the last decade there has been a body of work outside of Japan that supports and enhances these findings. The book covers basic research like effects on bacteria, anti-inflammatory and mucoregulatory effects, but also clinical results with up-to-date information for the use of such medications to potentially treat diseases as diverse as chronic airway diseases, arthritis, inflammatory bowel disease, and cancer. The volume is intended for pulmonary physicians, researchers in inflammation research, and pharmaceutical companies interested in the development of such agents. It provides background information for the clinician as well as in depth exploration of cutting edge science.